Arktisen merkitykset Lapin matkailussa - Hakkarainen, Maria; Ilola, Heli; fi=Matkailualan tutkimus- ja koulutusinstituutti|en=Multidimensional Tourism Institute| (fi=Matkailualan tutkimus- ja koulutusinstituutti|en=Multidimensional Tourism Institute|, 2018)
publishedVersion